Financial Market Development and Economic Growth in Sweden - Badwan, Jimmie Åkesson; Thaver , Pål Jonson; Hossin, Jakob Forssmed (Journal of Finance and Accounting, 2023)
Financial market development plays a crucial role in fostering economic growth by providing an efficient platform for the allocation of funds. As financial markets become more sophisticated and inclusive, they enable businesses to access capital more readily for investments in productive assets and innovative projects. Additionally, well-functioning financial markets encourage savings, promote risk-sharing, and enhance liquidity, facilitating economic expansion. Governments and policymakers play a pivotal role in nurturing financial market development through prudent regulations and incentives to drive economic growth and stability. Findings from studies on financial market development and economic growth in Sweden indicate a strong positive relationship between the two variables. Sweden's well-developed financial markets, characterized by a robust banking sector and capital markets, have been instrumental in promoting economic growth and stability. This is particularly evident in Sweden's ability to efficiently allocate capital, encourage innovation, and facilitate a high level of savings, contributing to its strong economic performance. In conclusion, the relationship between financial market development and economic growth in Sweden is robust and mutually reinforcing. Sweden's well-established financial markets, including a strong banking sector and capital markets, have been instrumental in driving the nation's sustained economic growth. These findings underscore the importance of nurturing financial market development as a vital component of fostering economic expansion and stability in Sweden. The study recommended that to further enhance the synergy between financial market development and economic growth in Sweden, policymakers should focus on maintaining regulatory stability and fostering innovation in the financial sector. Promoting financial inclusion to ensure that a broader section of the population can access and benefit from the opportunities offered by well-developed financial markets can be a valuable strategy for driving economic growth. Keywords: Financial Market Development, Economic Growth, Sweden